2013
DOI: 10.3109/09537104.2013.827783
|View full text |Cite
|
Sign up to set email alerts
|

Could mean platelet volume among complete blood count parameters be a surrogate marker of metabolic syndrome in pre-pubertal children?

Abstract: Interest in childhood metabolic syndrome (MetS) has increased substantially due to the increasing prevalence of childhood obesity on a global scale. Early recognition of MetS is critical in order to delay the development of cardiovascular disease (CVD). In this study, we evaluated the relationship between complete blood count (CBC) parameters and MetS among pre-pubertal children which may provide evidence in support of using low cost, readily available clinical haematological parameters for the detection of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…In addition, decreased MPV was regarded as an enhanced consumption of large PLTs in inflammatory states 30 ) . In fact, the results of our study were in concordance with the results of two recent studies 31 , 32 ) . In those studies, the researchers also found that MPV was significantly lower in obese female subjects and showed that MPV was inversely associated with the degree of obesity, independent of confounding factors.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, decreased MPV was regarded as an enhanced consumption of large PLTs in inflammatory states 30 ) . In fact, the results of our study were in concordance with the results of two recent studies 31 , 32 ) . In those studies, the researchers also found that MPV was significantly lower in obese female subjects and showed that MPV was inversely associated with the degree of obesity, independent of confounding factors.…”
Section: Discussionsupporting
confidence: 93%
“…So it can be deduced that PLT is positively correlated with MS in women. [ 16 , 40 , 41 ] Second, men are found to have higher MS prevalence than women due to lack of the protection of female sex hormone. [ 31 ] Female sex hormone is generally believed to decrease the risk of MS. Nagata et al [ 42 ] suggested that autocrine estradiol secretion could increase PLT production by triggering pro-PLT formation.…”
Section: Discussionmentioning
confidence: 99%
“…[5] The association of increased MPV, PDW, P-LCR, and platelet count with diseases related to endothelial dysfunction such as metabolic syndrome, diabetes, coronary artery disease (CAD), and malignancy has been shown in many studies. [6,7,8,9] The newer hematological analyzers are giving variety of platelet parameters which helps in easy detection of change in platelet structure, which may help in early detection of prothrombotic state of the platelets. These can act as an alarm for diagnosing initiation/progression of diabetic complications.…”
Section: Introductionmentioning
confidence: 99%